PELAKSANAAN PERJANJIAN SEWA MENYEWA RUKO MILIK PEMERINTAH DESA (STUDI DI DESA RUMAK) - Lalu Rizal Al Azhari; H. Zaenal Arifin Dilaga (Fakultas Hukum Universitas Mataram, 2021)
This research has the purpose to find out and explain the implementation of the lease agreement for shophouses between the village government and lessee, and find out and explain the dispute resolution on the lease agreement if the leaseholder leases again the object to another party. The implementation of the lease agreement for shophouses owned by the village government has been implemented by a written agreement, the lease agreement procedure for shophouses usually has been doing by Rumak Village people firstly by negotiation between the Rumak Village Government and the lessee. The dispute resolution if both parties have a dispute in this lease agreement between Rumak Village Government and the lessee, they have been doing by consensus discussion